SINTESIS ZEOLIT A BERBAHAN DASAR ABU TERBANG (FLY ASH) LIMBAH PT. INDONESIA CHEMICAL ALUMINA (ICA) MENGGUNAKAN METODE ALKALI HIDROTERMAL (SYNTHESIS OF ZEOLITE A BASE ON FLY ASH WASTE PT. INDONESIA CHEMICAL ALUMINA (ICA) USING HYDROTHERMAL ALKALINE METHOD) - Rizky Fitri Febrianti; Titin Anita Zahara; Adhitiyawarman Adhitiyawarman (Indonesian Journal of Pure and Applied Chemistry, 2022)
Fly ash is one of the combustion residues from coal-fired power plants which is produced in large quantities. The main elemental composition of fly ash is silica and alumina with content of 48.055% and 14.653%, respectively. This study aims to determine the characteristics of zeolite A synthesized from fly ash with various ratios of SiO2 and Al2O3. Zeolite A was synthesized using the alkaline hydrothermal method by varying the Si/Al molar ratio of 0.8 1 and 1.2. The initial process begins with the leaching process of fly ash waste and is followed by alkaline smelting. Furthermore, zeolite A was synthesized by adding sodium silicate and sodium aluminate to form a white gel. These steps were followed by a hydrothermal process using a hydrothermal autoclave at a temperature of 100֯C for 5 hours. Qualitative results on XRD showed that zeolite A synthesized at a ratio of Si/Al 1,2 had a 2ϴ position closer to standard zeolite A, which was seen based on the highest peaks at 2ϴ=12,420, 16,070, 20,360, 21,590, 23,960, 26,070, 27,080, 29,910, 32,500, 41,480, 44,090, 52,540, 54,230 and 66,660 and the structure formed is in cubic form with a crystallinity of 76.36%. Analysis using XRF showed that the Si/Al 1.2 ratio was the best for the formation of zeolite A. In this variation the silica and alumina content increased by 54.412% and 35.054%, respectively